2004
DOI: 10.4049/jimmunol.172.10.6167
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of Two Malaria Vaccine Candidate Antigens Enhances Product Yield, Immunogenicity, and Antibody-Mediated Inhibition of Parasite Growth In Vitro

Abstract: A Plasmodium falciparum chimeric protein 2.9 (PfCP-2.9) was constructed consisting of the C-terminal regions of two leading malaria vaccine candidates, domain III of apical membrane ag-1 (AMA-1) and 19-kDa C-terminal fragment of the merozoite surface protein 1 (MSP1). The PfCP-2.9 was produced by Pichia pastoris in secreted form with a yield of 2600 mg/L and ∼1 g/L of final product was obtained from a three-step purification process. Analysis of conformational properties of the chimeric protein showed that all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 28 publications
5
82
1
1
Order By: Relevance
“…The AM/ISA vaccine also induced appreciable levels of anti-MSP1 19 IgG, especially in the two animals that also had the highest anti-AMA1 IgGs in this group. Vaccine design studies with MSP1 19 fusion proteins have shown that IgG responses induced against the MSP1 19 component increase several fold compared to IgG responses to formulations with MSP1 19 alone [35,53], suggesting that fusion enhances antibody formation against the MSP1 19 component.…”
Section: Discussionmentioning
confidence: 99%
“…The AM/ISA vaccine also induced appreciable levels of anti-MSP1 19 IgG, especially in the two animals that also had the highest anti-AMA1 IgGs in this group. Vaccine design studies with MSP1 19 fusion proteins have shown that IgG responses induced against the MSP1 19 component increase several fold compared to IgG responses to formulations with MSP1 19 alone [35,53], suggesting that fusion enhances antibody formation against the MSP1 19 component.…”
Section: Discussionmentioning
confidence: 99%
“…Sero-epidemiologic evidence [35], and the limited GIA data presented here, suggest a PfAMA-1-based vaccine may elicit allele-specific antibodies. Consequently, in addition to monovalent PfAMA-1 vaccines [14][15][16][17]21] there are also bivalent PfAMA-1 vaccines in development in an effort to broaden protective immune responses [18,19,21]. With FMP2.1/AS02A, we intend to determine if high titer antibodies elicited against sporozoite and asexual stages, as well as potent anti-PfAMA-1 cellular responses, might act against diverse alleles.…”
Section: Pfama-1 Vaccine Designmentioning
confidence: 99%
“…Immunization of New World monkeys with recombinant PfAMA-1 formulated with Freund's adjuvant has conferred significant protection against homologous P. falciparum challenge [12,13], but limited protection when formulated with adjuvants intended for human use such as Montanide or AS02A [Barnwell, unpublished]. Several PfAMA-1 vaccines are in development, but none have been tested for clinical efficacy [14][15][16][17][18][19][20]. A recent Phase I clinical trial of a recombinant PfAMA-1 antigen adjuvanted with alhydrogel showed that this formulation elicited functional antibodies that, after affinity purification, exhibited growth inhibition of P. falciparum in vitro [21].…”
Section: Introductionmentioning
confidence: 99%
“…The two candidates (AMA-1 and MSP-1) enhance the product yield and immunogenicity of the individual components when combined. The protective immune responses induced by either AMA-1 or MSP1-19 are dependent on protein conformation (38).…”
Section: Multi-stage Multi-epitope/antigen Combination Vaccinesmentioning
confidence: 99%